Emigrar a Europa y escribir ficción. Los casos de Amara Lakhous y Gunter Silva Passuni (El Hilo de la Fabula, 2020)
This work aims to observe the texts of Amara Lakhous and Gunter Silva Passuni, two intellectuals —Algerian the former and Peruvian the latter— who share the decision of living abroad, having chosen Europe as their final destination (Italy and Great Britain respectively). Their literary production addresses the experience of being uprooted and the condition of the migrant, making it a space from which to look upon the nation of arrival, its inhabitants and social strata,emphasizing the multiple contradictions of this world. This context subverts —at least symbolically if not materially—the marginality of the migrant and calls into question the double absence that the Franco–Algerian sociologist indicated as a dramatic condition of every migrant worker.
Keywords: Contemporary literature; Latin American narrative; Italian narrative; Migrations; Gunter Silva Passuni; Amara Lakhous